UNLOCKING AVOCADO’S POTENTIAL: EXPLORING PREBIOTIC-INFUSED CELLULOSE MATRICES FOR PROBIOTIC STABILITY ENHANCEMENT - M., JATIN; ADHIKARI, BISHOP; J., ALIN BOSE; KUMAR, PIYUSH; RAJESHKUMAR, RAMAN (International Journal of Applied Pharmaceutics, 2025)
The stability and effectiveness of probiotics in functional foods and nutritional supplements are considerably influenced by their ability to survive harsh stomach conditions. The escalating interest in gut microbiome modulation has propelled the use of probiotics and prebiotics in functional food development. Avocados, rich in fibre and prebiotic properties, constitute an ideal basis for supporting the growth of the advantageous intestinal microbiota. The combination of prebiotics derived from the layer with cellulose matrices has shown improved probiotic survival rates, increased intestinal colonization, and an improvement in health benefits in preliminary studies. This new approach not only improves the stability of probiotics but also offers a further prebiotic effect that supports intestinal health. A schematic diagram illustrates the interplay between avocado-derived prebiotics, probiotics, and gut microbiota, enhancing conceptual clarity. The results suggest that this synergy could play a crucial role in the development of more effective and stable probiotic products for the nutraceutical and functional food industry. Future research must focus on the optimization of formulations, conducting large-scale clinical tests, and long-term benefits of these improved probiotic delivery systems. Future research should focus on personalized formulations and large-scale clinical validation to substantiate their therapeutic potential.